2020
DOI: 10.1186/s12943-020-01158-w
|View full text |Cite
|
Sign up to set email alerts
|

RNA demethylase ALKBH5 prevents pancreatic cancer progression by posttranscriptional activation of PER1 in an m6A-YTHDF2-dependent manner

Abstract: Background N6-methyladenosine (m6A) is the most abundant reversible methylation modification of eukaryotic mRNA, and it plays vital roles in tumourigenesis. This study aimed to explore the role of the m6A demethylase ALKBH5 in pancreatic cancer (PC). Methods The expression of ALKBH5 and its clinicopathological impact were evaluated in PC cohorts. The effects of ALKBH5 on the biological characteristics of PC cells were investigated on the basis of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
277
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(291 citation statements)
references
References 55 publications
14
277
0
Order By: Relevance
“…Subsequent correlation analysis also revealed that the two m 6 A-writers were inversely associated with immune cell infiltration. Inversely, the m 6 A RNA demethylase ALKBH5 exhibited an obvious enhancement in T lymphocyte infiltration and significant up-regulation in normal samples, indicating that the multiple types of post-transcriptional regulation underlay anti-tumor effects 76 , 77 . Together, these results suggest a diverse heterogeneity of m 6 A modification, demonstrating the importance of a comprehensive assessment of the m 6 A modification patterns and enhancing our understanding of epigenetic regulation on diverse physiological processes.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent correlation analysis also revealed that the two m 6 A-writers were inversely associated with immune cell infiltration. Inversely, the m 6 A RNA demethylase ALKBH5 exhibited an obvious enhancement in T lymphocyte infiltration and significant up-regulation in normal samples, indicating that the multiple types of post-transcriptional regulation underlay anti-tumor effects 76 , 77 . Together, these results suggest a diverse heterogeneity of m 6 A modification, demonstrating the importance of a comprehensive assessment of the m 6 A modification patterns and enhancing our understanding of epigenetic regulation on diverse physiological processes.…”
Section: Discussionmentioning
confidence: 99%
“…In pancreatic cancer, it was reported that METTL3 promotes cancer progression and chemo- and radio-resistance [ 34 , 48 ]. Although it was confirmed that ALKBH5 functions as a tumor-suppressor gene, involved in sensitizing pancreatic cancer cells to chemotherapy via direct impact on Wnt inhibitory factor 1, the m 6 A eraser was also reported to prevent pancreatic cancer progression by posttranscriptional activation of PER1 in an m 6 A-YTHDF2-dependent Manner [ 35 , 36 ]. Here, we present the first study on the expression of METTL14, one of the main m 6 A regulators, in pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that METTL3, ALKBH5 and YTHDF2 play important roles in pancreatic cancer cells [33][34][35][36]. However, the underlying mechanism by which aberrant m 6 A modifications facilitate the growth of pancreatic cancer has not been determined.…”
Section: Introductionmentioning
confidence: 97%
“…Among these, N6-methyladenosine (m6A) is the best understood and frequent mark of mRNA, and the functions of which ranges from pre-mRNA processing, translation, miRNA biogenesis to mRNA decay [30] . The importance of METTL3 and ALKBH5 in the development and progression of pancreatic cancer have pointed out [31 , 32] . By contrast, much less research has been conducted on m5C, which was detected in tRNAs and rRNAs and more recently in poly(A)RNAs.…”
Section: Discussionmentioning
confidence: 99%